Innovations in Digital Education: A Literature Review of Artificial Intelligence, Online Collaboration, and Digital Content Creation in Blended Learning - Rey L. Mapalad (Acta Pedagogia Asiana, 2026)
Digital transformation in education has accelerated the use of technologies such as artificial intelligence (AI), online collaboration tools, and digital content creation in teaching and learning. Blended learning, which combines face-to-face and online instruction, provides an effective framework for these innovations. This literature review synthesizes research on artificial intelligence applications, online collaboration platforms, and digital content creation, and examines their integration within blended learning environments. A systematic review of peer-reviewed studies published between 2015 and 2025 was conducted using Google Scholar, Education Resources Information Center, Scopus, ScienceDirect, and JSTOR. Sixty articles were selected and analyzed thematically under four themes: artificial intelligence in education, online collaboration, digital content creation, and their integration within blended learning. The findings show that artificial intelligence enhances personalized learning, online collaboration fosters interaction and teamwork, and digital content creation supports engagement and knowledge retention. When combined within blended learning, these innovations improve flexibility, accessibility, and overall learning outcomes. However, challenges such as the digital divide, teacher readiness, infrastructure limitations, and data privacy concerns remain significant. The integration of artificial intelligence, collaboration tools, and digital content creation offers substantial potential to advance student-centered education. Strategic investments in teacher training, infrastructure, and supportive policies are essential to fully leverage digital transformation and develop future-ready education systems.